Clinical use of an analysis of oxidative stress and IL-6 as the promoters of diabetic polyneuropathy - Emina Karahmet; Besim Prnjavorac; Tamer Bego; Adaleta Softić; Lejla Begić; Edin Begić; Esma Karahmet; Lejla Prnjavorac; Irfan Prnjavorac (Medicinski glasnik, 2020)
Aim: To investigate interleukin 6 (IL-6) values depending on duration of diabetes mellitus (DM) and evaluate possible correlation with diabetic polyneuropathy. Methods: The research study included 90 patients with DM divided into three groups (30 patients each) according to the duration of DM: group A - patients who had DM for less than 10 years, group B - duration of DM was 10 to 20 years, and group C - patients with DM over 20 years. Control group (K) included 30 healthy participants. Results: IL-6 was significantly higher in the healthy control group, 180.318 pg/mL±94.18, than in group A, 47.23pg/ml±34.8, group B, 43.31pg/ml±33.17, and group C, 70.39 pg/ml±59.26 (p=0.0001). All groups had significantly different values of IL-6 between each other (p=0.0001). Level of IL-6 was in correlation with diabetic polyneuropathy in the group A (the youngest participants) (p=0.0001). In other groups there was no significant correlation between IL-6 and diabetic polyneuropathy. Conclusion: The level of IL-6 was in correlation with neuropathy among younger patients. A higher level of IL-6 in the control group than in diabetic groups is a sign of stronger inflammatory response among younger and healthy people than in patients with DM.
Keywords: diabetes; interleukins; inflammation; neuropathy